A cross-sectional study of thyroid autoimmunity in women with type 2 diabetes: case for routine thyroid dysfunction screening - Surekha Bhujanga Shetty; Lalitha Ramachandrappa (International Journal of Medical Research and Review, 2019)
Introduction: Subjects with diabetes have a higher prevalence of thyroid disorders compared to the general population. The reported prevalence of thyroid disorders is 10-24% in subjects with diabetes and 6 - 13% in subjects without diabetes. Auto immunity is held responsible for the increased prevalence of thyroid dysfunction in diabetes. Studies have proven the higher rates of autoimmune thyroid dysfunction in type 1 diabetes, but there is very little information regarding thyroid autoimmunity in type 2 diabetes.Objective: To estimate the prevalence of thyroid dysfunction and thyroid autoimmunity in women with type 2diabetes.Material and Methods: Samples for thyroid function test including free thyroxin (fT4), thyroid stimulating hormone (TSH) and thyroid peroxidase antibodies (anti -TPO) were obtained from 100 women with type 2 diabetes, attending the outpatient department of Karnataka Institute of Endocrinology and Research, Bangalore.Results: Thyroid dysfunction was found in 42% subjects, where 36% had subclinical hypothyroidism and 6% had overt hypothyroidism. Anti - TPO positivity was seen in 30% of the subjects. Anti-TPO positivity was found in 24.1% euthyroid subjects, 33.3% subclinical hypothyroid subjects and 66.7% overt hypothyroid subjects. Significant positive correlation was observed between anti-TPO and TSH (p value <0.001*). No statistically significant association was found between thyroid dysfunction and age, BMI, Hba1c, and diabetes duration.Conclusions: The prevalence of thyroid dysfunction is significantly high in women with type 2 diabetes. The most common abnormality is subclinical hypothyroidism and autoimmunity is the cause of thyroid dysfunction in large proportion of these subjects.